Estimulación temprana y el desarrollo socio afectivo de los niños y niñas del nivel inicial i del centro de educación inicial “Pio Jaramillo Alvarado”, de la ciudad de Loja. Período lectivo 2014-2015. Lineamientos propositivos - Sánchez Roma, Tatiana del Cisne (2015)
This investigation is related to "EARLY LEARNING AND SOCIO - AFFECTIVE DEVELOPMENT OF ONE INITIAL LEVEL CHILDREN OF “PIO JARAMILLO ALVARADO “CHILDHOOD EDUCATION CENTER LOJA CITY PERIOD 2014-2015. PROPOSITIONAL GUIDELINES. It is the focus of this research work. Therefore I thought to pose the following question: How does early learning and socio - affective development of one initial level children of “Pio Jaramillo Alvarado “childhood education center Loja city period 2014-2015. Propositional guidelines? The General Objective was to determine the Early Learning and Socio-Affective Development of one initial level children of "Pio Jaramillo Alvarado" childhood education Center Loja city. The methods used were: Scientific, Inductive, Deductive, Analytical and Descriptive Synthetic; the same that were used to achieve the objectives. The techniques and instruments used were: a Survey applied to the teacher of the Initial Level I "Pio Jaramillo Alvarado" to establish the activities and strategies of early stimulation that applies in your Daily Working Hours; Test Ebee and León Gross, aimed at parents of children to assess the children socio – affective Development. The Teacher’s Survey Results determined that 100% engaged activities with Early Stimulation, in order to enhance the full potential and skills in their areas, physical, intellectual, motor, body and particularly the Socio-Affective area, as enhance the socio-affective, letting children relate in better way with their parents. Application of the Test of León Gross Ebee aimed at Family parents found that 59% scored zero and five negative responses equivalent to Very Satisfactory, this shows that children are gaining control of his body and the world around them according to their age, 41% scored between five and fifteen negative responses, equivalent to Satisfactory in this case parents should be calm and maintain surveillance of the attitudes and perceptions of the child so that it does not produce any delay.